The Chinese waste import ban and the emergence of waste havens within Europe - Konstantin Sommer (Tinbergen Institute, 2024)
We study the implications of the Chinese waste import ban of 2018 on intraEuropean plastic waste trade. Specifically, we ask if it led to a "waste haven" effect, which would imply that countries with high disposal and recycling costs started to export more plastic waste to countries with lower costs. We study this question in a gravity difference-in-differences setting with detailed data on the costs of waste processing. We find strong evidence that countries with higher costs of disposal indeed started to export more waste towards lower cost countries as a result of this ban. We do not find consistent evidence that more waste was exported to countries with lower recycling costs. Our results raise distributional questions about the allocation of waste externalities in integrated markets and have implications for current debates on the legislation of international waste shipments.
Keywords: F18; Q53; Q27; 330; Trade; Environment; Waste; Circular Economy; Europe